(untitled) (Private Law, 2025)
The purpose of the study is to determine the implementation of legal responsibilities and the obstacles in carrying out responsibilities and how the dispute resolution. The type of research is empirical legal research. In this research, the author uses three approach methods, namely the statute approach, conceptual approach, and sociological approach. The results of this research show the implementation of PO DUNIA MAS legal responsibilities is concerned with the safety of its passengers and vehicle crew in providing compensation or insurance. For Raharja Insurance Services, they are providing compensation in accordance with the losses by passengers and vehicle crews. The obstacles to PO. Dunia Mas are delays and lack of time discipline, lack of cargo discipline, inconvenience, and security disturbances.